PENDAMPINGAN PENERAPAN MODEL PEMBELAJARAN TEMATIK SIAP SIAGA BANJIR UNTUK MENUMBUHKAN SIKAP KESIAPSIAGAAN BENCANA BANJIR SISWA KELAS IV SDN 89 KOTA BENGKULU - Dalifa, Dalifa; Hasnawati, Hasnawati; Yuliantini, Nani; Agusdianita, Neza (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The school that is being used as a partner for the Community Service (PKM) activity that is being proposed is SDN 89. SDN 89 Bengkulu City, Bentiring Village is one of the schools that is most frequently flooded. The purpose of this activity is to train and assist teachers in designing, implementing and evaluating flood preparedness thematic learning models to foster flood preparedness attitudes for elementary students. The method used in this PKM activity is training and mentoring. The result of the activity is that training and mentoring activities have been carried out on November 4, 2021. The product of this PKM activity is a draft of thematic learning tools ready for flood disaster. It is hoped that by integrating flood disaster preparedness attitudes to elementary school students will provide knowledge and skills about preparedness before a flood disaster, during a flood disaster and after a flood disaster